"Just Do It? An Examination of Race on Attitudes Associated with Nike's Advertisement Featuring Colin Kaepernick". Issue 10 (2nd October 2020) - Intravia, Jonathan; Piquero, Alex R.; Leeper Piquero, Nicole; Byers, Bryan
ABSTRACT: The relationship between race and just about any social issue has been and continues to be controversial. Within the context of literature on public opinion regarding sports and social movements, this study considers the intersections between race, business, and athlete activism by examining attitudes related to Nike's controversial advertisement campaign with former NFL quarterback Colin Kaepernick. Results obtained from a sample of young adults reveals a deep racial divide between black and non-black respondents. At almost a ratio of 2:1, blacks were more likely to agree with Nike's decision to use the former player in their advertisement, that Nike should address social issues in their ads, and that Nike should contribute to his charity. These race differences remain in models that control for a variety of other correlates, including political orientation, income, discrimination, player protests, and whether they watch the NFL.